Survei Minat Siswa pada Pembelajaran Penjas di SMK Negeri 1 Kota Palangka Raya - Cukei; Abdul Kasir (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
Physical education learning is still not running smoothly and not as expected. Students who still often do not focus when the teacher is explaining the material in the room or in the field so that students do not understand the explanation given by the teacher. Some students are embarrassed to ask which parts are not clear and understand so that when they do the movements in the Physical Education material, they become confused. This study aims to determine students' interest in physical education learning at SMK Negeri 1 Palangka Raya City This study uses a survey method. The population and sample in this study were all students of class X and XI as many as 173 people. The variable in this study is the students' interest in participating in physical education learning. The sampling technique used was total sampling. Data collection using a questionnaire was analyzed with descriptive statistics of percentages. The results of the survey research on student interest in Physical Education learning at SMK Negeri 1 Palangka Raya City are included in the high category, which is indicated by high attitudes, desires, perseverance and encouragement. Students in participating in Physical Education learning can master Physical Education learning and have physical fitness and become the best in learning Physical Education. It can be concluded that students' interest in Physical Education Learning is in the high category, namely 78.1% with details of 86.4% for the attitude aspect, 75.8% desire, 68.3% perseverance and 78% encouragement. In connection with students' interest in Physical Education in the high category, it is recommended that the school completes facilities and infrastructure so that students can achieve optimally, besides that the creativity of physical education teachers is also highly expected.